Study of Application of Green Business Model with Reference to I.T Sector - Luhar, Arvind S.; Memon, Aksha (SFIMAR Research Review, 2016)
A green business will engage in forward thinking policies for environmental concerns and policies affecting human rights. Many businesses are talking the GREEN TALK, but are they really walking the GREEN WALK?? A Green Business or sustainable business defined " as one that strives to reduce its negative impact on the local environment, community, society or economy while maintaining a profit". Quantitative analyses on the performance and effects of the green business models are scarce and a critical level of knowledge for Green concept. .Green business models focuses on ; Functional Sales, Energy Saving Companies (ESCO), Chemical Management Services (CMS), Design, Build, Finance and Operate (DBFO) and Sharing. The researcher tries to find out the solution on the problems related to awareness and implementation of Green Business Model and its effect on environmental issues. This is based on primary study. It descriptive study analysis with the help of Chi square test. The researcher proposed to explain concept, benefits and issues pertaining to implementation of Green Business Model through the study.